Responding to negative hotel reviews: A cross-linguistic perspective on online rapport-management. (October 2020) - Cenni, Irene; Goethals, Patrick
Abstract: Responses from business embody a new and productive CMC genre, also known as 'webcare'. In this contribution we investigated responses written by hotels to negative reviews posted on TripAdvisor. More specifically, we analyzed a total number of 300 responses written in three languages, namely English, Dutch and Italian, focusing on a cross-linguistic perspective. Discourse characteristics of these emergent CMC texts have been examined. First, we carried out an analysis of the rhetorical moves structuring the responses in the three languages under examination. Second, we analyzed the responses from a qualitative point of view, using the conceptual framework of Rapport-Management Theory (RMT, Spencer-Oatey, 2008). Results brought to light a substantial similarity between English and Dutch responses in terms of communicative strategies, while consistent divergences have been found in the Italian subset. In particular, dismissing the tourists' complaints, through moves as denying the service failure, shifting responsibility to others and providing justifications, seem to be linguistic strategies adopted mostly by Italian response writers when compared to the other subsets. These findings suggest how Italian response writers are less concerned with the restoration of customers' satisfaction and their 'sociality rights' (Spencer-Oatey 2008), preferring a more confrontational and defensive style when addressing a service failure.